Age-dependent acquired protection against Plasmodium falciparum in people having two years exposure to hyperendemic malaria. - Baird, J; Jones, T; Danudirgo, E; Annis, B; Bangs, M; Basri, H; Purnomo; Masbar, S (1991)
An epidemiologic study of susceptibility to frequent and high-grade parasitemia by Plasmodium falciparum revealed that age-dependent acquired protection developed within a two-year period of exposure to hyperendemic infection pressure. The study was conducted in a single village in northeastern Irian Jaya, Indonesia, where half the residents were native to the province and the other half were transmigrants from areas of Java, where there is little or no malaria transmission. Five separate measures of susceptibility to the asexual parasitemia of falciparum malaria were derived from results of four months of biweekly surveillance of 240 volunteers. Increasing protection as a function of age among the Javanese was a consistent pattern among the five estimates of susceptibility. These age-dependent functions of protection were quantitatively parallel to those among life-long residents of Irian Jaya. When humoral immune responsiveness to ring-infected erythrocyte surface antigen (RESA) was measured by ELISA, a similar pattern emerged; the relative level of antibody to RESA increased as parallel functions of age among the two subpopulations. Acquired protective immunity against P. falciparum was not the cumulative product of many years of heavy exposure to antigen. Instead, the full benefit of protection appeared to develop quickly. The degree of protection was governed by recent exposure and age, independent of history of chronic heavy exposure.